Interview: the evolution of regulation from a global perspective and its contemporary challenges - Baldwin, Robert (2025)
In the context of the evolution of regulation as a discipline, its characteristics that distinguish it from administrative law and the state’s police powers are explored. The main theoretical approaches to the regulatory process are addressed, such as public interest, interest groups, and institutional models. These models provide various explanations for the development of regulatory policies, which may vary depending on the context and circumstances.Additionally, in light of contemporary challenges, the responses of regulatory authorities to situations arising from the COVID-19 pandemic, digitalization, artificial intelligence (AI), and cryptocurrencies are analyzed. The most effective regulatory models for addressing these challenges are evaluated, highlighting the importance of  flexible and adaptive regulation in response to global risks. Finally, the need for future legal professionals to develop interdisciplinary skills is emphasized, as this will enable them to address regulatory complexities in an ever-changing world.